2019
DOI: 10.1111/lam.13163
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of Mimosa caesalpiniifolia Benth and its interaction with antibiotics against Staphylococcus aureus strains overexpressing efflux pump genes

Abstract: This study aimed to evaluate the antimicrobial activity of the dichloromethane fraction (DCMF) from the stem bark of Mimosa caesalpiniifolia and its effect on the activity of conventional antibiotics against Staphylococcus aureus strains overexpressing specific efflux pump genes. DCMF showed activity against S. aureus, Staphylococcus epidermidis and Candida albicans. Addition of DCMF at subinhibitory concentrations to the growth media enhanced the activity of norfloxacin, ciprofloxacin and ethidium bromide aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…A further investigation verified that 4,5,6,7-tetramethoxyflavone, the most methoxylated molecule, exhibited the highest modulating agent performance, reducing the minimal inhibitory concentration of norfloxacin against S. aureus SA1199B by a factor of 16 [47]. However, quercetin, which is a flavonoid analogue of retusin without methoxy groups, has been reported as a TetK and NorA inhibitor [48], suggesting that the mere Attenuation of bacterial drug resistance has been reported for different plant species [49,50]. For Croton species, it has been demonstrated that volatile components from the essential oil of Croton zehntneri potentiate the gentamicin activity against Pseudomonas aeruginosa [40], as well as the norfloxacin activity against S. aureus SA1199B [51].…”
Section: Resultsmentioning
confidence: 95%
“…A further investigation verified that 4,5,6,7-tetramethoxyflavone, the most methoxylated molecule, exhibited the highest modulating agent performance, reducing the minimal inhibitory concentration of norfloxacin against S. aureus SA1199B by a factor of 16 [47]. However, quercetin, which is a flavonoid analogue of retusin without methoxy groups, has been reported as a TetK and NorA inhibitor [48], suggesting that the mere Attenuation of bacterial drug resistance has been reported for different plant species [49,50]. For Croton species, it has been demonstrated that volatile components from the essential oil of Croton zehntneri potentiate the gentamicin activity against Pseudomonas aeruginosa [40], as well as the norfloxacin activity against S. aureus SA1199B [51].…”
Section: Resultsmentioning
confidence: 95%
“…Apart from phage endolysins, identifying efflux pump inhibitory molecules, e.g., P-glycoproteins, would be another approach to combat the continuous rise of MDR pathogens [35]. In addition, an array of recent studies has also demonstrated that some natural products such as DCMF from M. caesalpiniifolia and P. amarus ethanoic extracts could function as pump inhibitors and interact with conventional antibiotics fighting against pathogenic resistance [36,37]. These natural or synthetic pumps inhibitors can also be covalently joined together as a hybrid, which indeed showed surprisingly in vitro and in vivo antimicrobial activity [38].…”
Section: Discussionmentioning
confidence: 99%
“…The combinations showed synergistic and indifferent effects (Braga et al, 2005). Silva et al (2019) studied the antibacterial activity of the dichloromethane fraction (DCMF) from the stem bark of Mimosa caesalpiniifolia and its effect on the activity of conventional antibiotics against Staphylococcus aureus strains overexpressing specific efflux pump genes. They concluded that such compounds could be used as adjuvants of norfloxacin, ciprofloxacin or tetracycline for treatment of infections caused by S. aureus strains overexpressing efflux pumps (S. W. C. Silva et al, 2019).…”
Section: In Vitro Interaction Assaymentioning
confidence: 99%
“…Additionally, the A. colubrina bark is used as folk medicine for infections and inflammation and there are scientific evidence showing its potential for fighting microorganisms (A. R. N. Lima et al, 2020;R. D. F. Lima et al, 2014;S. W. C. Silva et al, 2019;Weber et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation